Educación Ambiental y actitudes frente a la naturaleza, en los niños/as del quinto grado de Educación General Básica, de la escuela “Reino de Bélgica” del cantón Guano en el período lectivo 2022-2023. - Balseca Méndez, Mariana Natali (2024)
The objective of this study was to investigate the importance of Environmental Education in the formation of attitudes towards nature in boys and girls in the fifth grade of Basic General Education, of the “Reino de Belgica” School in the Guano canton in the period school year 2022-2023. For which, a mixed approach was used, combining qualitative and quantitative methods, the type of research was non-experimental field and in which bibliographic methods were used, the population included the 8 eight grade students of basic education. In the qualitative aspect, an interview was carried out with the teacher to identify the contents, resources and methodology related to environmental education. On the other hand, in the quantitative approach, the student survey was used in order to obtain information about their attitudes. The results revealed that teachers apply the contents of Environmental Education following the guidelines of the Ministry of Education, with emphasis on environmental problems and the loss of biodiversity. However, the lack of implementation of the "Land of girls, boys and young people for Good Living" (TiNi) space was identified. Regarding the students' attitudes, it was observed that they have a positive predisposition towards caring for the environment, which suggests that they understand the importance of environmental education, but do not always apply it in their daily actions.